«Ծաւդէացւոց իշխանութիւն » - Ս. Տ. Երեմյան (ՀՍՍՌ ԳԱ հրատ․)
В „Истории Армении" Мовсеса Хоренаци Кадмос является этнонимом области „Дом Кадмоса",которую Г. А. Капанцян справедливо отождествляет с „Кадмухи" ассиро-вавилонских источников. В античных источниках эта область известна под именем Zabdicenae, в армянских-Цавдэк. Помимо „Дома Кадмоса" существовал также „Удел Кадмосидов" (Կադմեանք)по соседству с Сюнией. Последний отождествляется с ишханством Цавдейским (Мовсес Хоренаци II, 8) на северо-востоке Армении—между областями Сюник, Утик, Гардман и областью Гаргареев (Каспианой).In the „History of Armenia" by Movses Khorenatzi Cadmos is an ethnonym for the province „Home of Cadmos", which G. A. Kapantzian truly identifies with „Kadmukhi" in the Assyro-Babilonian sources. In the antique sources this province goes under the name Zabdicenae, in armenian ones — Tzavdeck. Beside the „Home of Cadmos" there also existed the „Appanage of Cadmosides" in the vicinity of Syunia. The latter is identified with the „ishkhanate of Tzavdey" (Movses Khorenatzi II, 8) on the north-east of Armenia — between the provinces Syunick, Utick, Gardman and that of the Gargareys (Caspiana).
Keywords: Պատմություն